2020
DOI: 10.4187/respcare.07663
|View full text |Cite
|
Sign up to set email alerts
|

Year in Review 2019: High-Flow Nasal Cannula Oxygen Therapy for Adult Subjects

Abstract: Many high-quality clinical trials and meta-analyses on the utilization of high-flow nasal cannula for adult patients have been published in the last 2 years. This review summarizes the recent clinical evidence, with the aim to provide the currently available evidence regarding the utilization of high-flow nasal cannula for the adult patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 70 publications
1
32
0
1
Order By: Relevance
“…Oxygen delivery via HFNC has become widely used in patients with acute hypoxemic respiratory failure due to its benefits of meeting or exceeding patient inspiratory flow demand, reducing oxygen dilution, and washing out pharyngeal dead space [ 55 ]. HFNC has been shown to reduce the need for endotracheal intubation when compared to conventional oxygen delivery devices [ 56 ].…”
Section: Literature Findings and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen delivery via HFNC has become widely used in patients with acute hypoxemic respiratory failure due to its benefits of meeting or exceeding patient inspiratory flow demand, reducing oxygen dilution, and washing out pharyngeal dead space [ 55 ]. HFNC has been shown to reduce the need for endotracheal intubation when compared to conventional oxygen delivery devices [ 56 ].…”
Section: Literature Findings and Suggestionsmentioning
confidence: 99%
“…Pre-oxygenation prior to intubation plays a crucial role in avoiding complications during intubation. Multiple randomized controlled trials have shown that the utilization of HFNC for pre-oxygenation can help reduce the incidence of hypoxemia during intubation [ 55 , 80 ]. The cost-effectiveness and the high risk of transmission from high gas flows should be taken into consideration before using it for pre-oxygenation prior to intubation.…”
Section: Literature Findings and Suggestionsmentioning
confidence: 99%
“…5 6 In hypoxaemic respiratory failure, HFNC use is associated with lower mortality, lower rates on endotracheal intubation and improved oxygenation. [7][8][9] It has been extensively used early in the COVID-19 outbreak in China. 10 Prone positioning (PP) of mechanically ventilated patients is an effective first-line Strengths and limitations of this study ► This pragmatic design will deal with the recruitment difficulties that could occur in the individual trials given the uncertainties of the international dynamics of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…High‐flow nasal cannula (HFNC) oxygen therapy has increased in popularity in recent years due to its superiority over conventional oxygen therapy in reducing treatment failure, particularly among small children 1 . The utilization of HFNC has also been expanded from critical care units to general care wards, emergency departments, and procedure rooms 2 . There are several known physiologic benefits of HFNC oxygen therapy: meeting and/or exceeding patient inspiratory flow, providing a constant fraction of inspired oxygen (F I O 2 ) and a small amount of positive airway pressure, and washing out the anatomic dead space 1‐3 .…”
mentioning
confidence: 99%